2016
DOI: 10.1080/19443994.2015.1072739
|View full text |Cite
|
Sign up to set email alerts
|

Integration of CFD and RTD analysis in flow pattern and mixing behavior of rotary pressure exchanger with extended angle

Abstract: A B S T R A C TIn this study, the computational fluid dynamics (CFD) approach combined with the residence time distribution (RTD) analysis was implemented to examine the mixing performance and flow pattern of rotary pressure exchanger (RPE). Based on oscillatory Reynolds number, a flow regime classification was established for RPE. A concept of extended angle of RPE was proposed, and then, its effects on mixing behavior were evaluated by CFD simulation in laminar model. Meanwhile, flow pattern in RPE was quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…The change in the inclination angle or extended angle results in a change in the rotary speed at the same flow rate; thus, ξ and the mixing rate vary. To decrease the mixing rate of an RERD, the rotary speed needs to be increased at the same flow rate, implying that self-driven hydraulic efficiency should be improved.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in the inclination angle or extended angle results in a change in the rotary speed at the same flow rate; thus, ξ and the mixing rate vary. To decrease the mixing rate of an RERD, the rotary speed needs to be increased at the same flow rate, implying that self-driven hydraulic efficiency should be improved.…”
Section: Resultsmentioning
confidence: 99%
“…Mei et al 16 proposed a method to predict how long it took for the mixing zone to propagate to the ends of the channel. Cao et al 17 proposed an extended angle concept for the RERD and investigated its influence on the mixing rate via CFD simulation. They found that at an extended angle of ±30°, the minimum mixing rate was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Here, VRTD is used to assess the degree of flow non-uniformity and how far the flow deviates from the ideal plug flow. The smaller the VRTD, the closer is the flow pattern to an ideal plug flow [33]. In this article, a series of cross sections along the axial direction were created and the tracer concentrations versus the time were monitored.…”
Section: Rtd By the Tracer Methodsmentioning
confidence: 99%
“…Die Auslegungsparameter dieser Energierückgewinnung folgen aus denen der RO‐Anlage. Dabei können beim Druckaustausch zwischen dem Konzentrat‐ und dem RO‐Feedstrom, der durch den Druckaustauscher geleitet wird, sehr niedrige Vermischungen auftreten , ; dies wird hier aber nicht unterstellt.…”
Section: Vorgehensweiseunclassified